The law of evidence in Canada - Lederman, Sidney N.; Fuerst, Michelle K.; Stewart, Hamish (LexisNexis, 2022)
"This comprehensive treatise covers both civil and criminal law evidence. The book is written for lawyers, judges and students, and covers evidence law topics such as standards of proof, hearsay, similar fact evidence, opinion evidence, witnesses, privilege, and admissibility of evidence."– Provided by publisher.
QID: Q135479502